MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU - Nugraha, Doni; Ade Nursamsudin, Ujang (Program Studi Manajemen Pendidikan Islam, 2025)
The head of the madrasah is one of the components of education that influences the improvement of teacher performance. Therefore, the success of the head of the madrasah in implementing management is very important to improve the quality of education in the madrasah, especially in the Learning Process carried out by teachers. This study attempts to reveal how the management of the principal improves teacher performance. This study uses a qualitative research type with a qualitative method. The researcher here uses a field research approach. Research with the aim of describing a population, situation, phenomenon, accurately and systematically. While the data analysis uses through Observation, Interviews, Documentation, data presentation, and drawing conclusions. The conclusion of the study shows that: 1) The Head of the Madrasah is responsible for the planning, organizing, implementing, and supervising the madrasah, including administration. 2) Teacher performance at MA Almunir is very important and involves planning, implementing, and evaluating learning. Teachers are able to prepare RPP well, choose the right method, and conduct evaluations. 3) The management of the head of the madrasah at MA Al Munir, Burujuljaya Village is seen in the planning, organizing, implementing, and evaluating teacher performance. The vision and mission of the Madrasah are decided together. Organization starts from recruitment to assignment according to needs. The head of the madrasah supervises teacher performance, with the aim of improving the quality of education at MA Al Munir, Burujuljaya Village. 4) Supporting factors for the implementation of madrasah head management in improving teacher performance include facilities and infrastructure that are in accordance with the quality of education. 5) The head of the madrasah at MA Al Munir, Burujuljaya Village has duties and strategies to improve teacher performance with positive management, which has an impact on student achievement and school success.